DYNAMIC RESPONSE ANALYSES OF COLLINEAR BARS WITH CONCENTRATED MASSES - LIU XinQin (Jixie qiangdu, 2015)
Longitudinal vibration of the elastic bars with concentrated masses widely exist in the engineering applications which needs to be studied deeply. In this paper,the harmonic dynamic disturbance was considered. At first,the equations to be determined were written out,the linear algebraic equations of the unknown coefficients were obtained utilizing the supposed harmonic solutions with unknown coefficients,boundary conditions of the problem and the dynamic conditions of the concentrated masses. The given example took three bars and two concentrated masses as the example,the vibration displacement amplitudes and the dynamic stress amplitudes of the bars along the axial direction with different disturbance frequencies were studied,The conclusions can provide the theoretical bases for the dynamic strength check and the strength design.